Halving hunger : it can be done - Sánchez, Pedro A., 1940-; Swaminathan, M. S. (Monkombu Sambasivan); Dobie, Philip; Yuksel, Nalan (Earthscan, 2005)
The Millennium Development Goals adopted at the UN Millennium Summit in 2000 are the world's targets for dramatically reducing extreme poverty in its many dimensions by 2015--income poverty hunger disease exclusion lack of infrastructure and shelter-while promoting gender equality education health and environmental sustainability. These bold goals can be met in all parts of the world if nations follow through on their commitments to work together to meet them. Achieving the Millennium Development Goals offers the prospect of a more secure just and prosperous world for all. The UN Millennium Pro.